2011
DOI: 10.1007/s10812-011-9446-5
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bonds of anti-HIV active aminophenols

Abstract: Analysis of IR-Fourier spectra from solutions and crystals of antiviral sulfo-containing aminophenols has shown that various types of intramolecular and intermolecular interactions can occur in molecules of these compounds. Three types of intramolecular hydrogen bonds (O-H⋅⋅⋅N, O-H⋅⋅⋅O=S=O, and N-H⋅⋅⋅O=S=O) are formed in CCl 4 solutions of the sulfo-containing aminophenols. The formation of intermolecular H-bonds involving the NH-and OH-groups and the preservation of the intramolecular O-H⋅⋅⋅O=S=O H-bond are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The study of the IR spec tra of 10 -3 M CCl 4 solutions of all eight sulphone con taining aminophenols has shown that the absorption bands with the frequencies of their maxima ν max = 3638, 3425, and 3250 cm -1 are caused by stretching vibrations of free and associated OH groups, while bands with ν max = 3510 and 3360 cm -1 occur due to free and coupled vibrations N-H [7,14].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study of the IR spec tra of 10 -3 M CCl 4 solutions of all eight sulphone con taining aminophenols has shown that the absorption bands with the frequencies of their maxima ν max = 3638, 3425, and 3250 cm -1 are caused by stretching vibrations of free and associated OH groups, while bands with ν max = 3510 and 3360 cm -1 occur due to free and coupled vibrations N-H [7,14].…”
Section: Resultsmentioning
confidence: 99%
“…Aminophenol compounds were synthesized according to techniques described in [7]. The correct ness of the chemical structure of synthesized ami nophenol derivatives was confirmed by data of mass spectrometry, NMR, and elemental analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Conditions for the formation of intramolecular HBs are created in phenols with several OH groups and electronegative atoms such as N and O located in the ortho-position to one of the hydroxyls [8][9][10][11][12]. Therefore, the AB with ν max = 3464 cm -1 in the IR spectrum of BA I in CCl 4 (Table 1) were observed in the IR spectrum of BA I crystal (Fig.…”
mentioning
confidence: 95%
“…As a rule, vibrations of free OH groups in spectra of phenols appear in the range 3640-3600 cm -1 [12,13]. It is noteworthy that phenol hydroxyls are not involved in IeI that form HBs at concentrations ≤3⋅10 -3 M in neutral solvents [8][9][10][11][12].…”
mentioning
confidence: 99%